Investigation of the regulatory effects of water and nitrogen supply on nitrogen transport and distribution in wolfberry fields - Tian, Rongrong; Wang, Jinghai; Yin, Minhua; Ma, Yanlin; Jia, Qiong; Kang, Yanxia; Qi, Guangping; Gao, Yalin; Jiang, Yuanbo; Li, Haiyan; Xiao, Feng (Frontiers in Plant Science, 2024)
Resource-based water shortages, uncoordinated irrigation, and fertilization are prevalent challenges in agricultural production. The scientific selection of appropriate water and fertilizer management methods is important for improving the utilization efficiency of agricultural resources and alleviating agricultural non-point source pollution. This study focused on wolfberry and compared the effects of four irrigation levels [W0 (75%–85% θf), W1 (65%–75% θf), W2 (55%–65% θf), and W3 (45%–55% θf)] and four nitrogen application levels [N0 (0 kg·ha−1), N1 (150 kg·ha−1), N2 (300 kg·ha−1), and N3 (450 kg·ha−1)] on soil nitrate nitrogen (NO3−–N) transport, plant nitrogen allocation, and soil nitrous oxide (N2O) emissions during the harvest period of wolfberry. And this study used CRITIC-entropy weights-TOPSIS model to evaluate 16 water and nitrogen regulation models comprehensively. The results revealed the following: (1) The average NO3−–N content in the 0–100 cm soil layer ranged from 3.95–13.29 mg·kg−1, indicating that W0 > W1, W2, W3, and N3 > N2 > N1 > N0. (2) The soil NO3−–N accumulation ranged from 64.45–215.27 kg·ha−1 under varying water and nitrogen levels, demonstrating a decreasing trend with increasing horizontal distance. The NO3−–N accumulation at each horizontal distance increased with increasing irrigation and nitrogen application. (3) The total nitrogen content and nitrogen uptake in all wolfberry organs were W1 > W0 > W2 > W3, and N2 > N3 > N1 > N0. (4) The emission flux and total emission of N2O increased with increasing irrigation and nitrogen application. The changes of N2O emission intensity were inconsistent with increasing irrigation and nitrogen application. The maximum emission intensity was observed under the W3N3 treatment (0.23 kg·kg−1). The N2O emission coefficients ranged from 0.17–0.39%, in the order of W0 > W1 > W2 > W3 (except for N1) and N1 > N2 > N3. The comprehensive evaluation revealed that W1 (65%–75% θf) combined with N2 (300 kg·ha−1) decreased soil NO3−–N leaching, increased nitrogen uptake, and reduced N2O emission. These findings can serve as a reference for improving the efficiency and reducing emissions of wolfberry in the Yellow River irrigation region of Gansu Province and in similar climate zones.